Examining the Equivalents of the Phrase "Be'ghayr-i Hesāb" (without calculation) in the Qur'an: A case study of translators (Mousavi Hamedani, Elahi Ghomshei, Khorramshahi, Fooladvand, Ansarian, Ayati) - Qorbani Laktarashani, Fatemeh; Halimi Jeloudar, Habibollah (Iranian Journal of Translation Studies, 2022)
Semantic equality and the selection of appropriate equivalents under words and phrases are among the issues that should be considered in translating texts. Matter of (hā, sin, bā) has been used in the Qur'an with relatively high frequency and in various semantic ranges. This research descriptively-analytically examines the translations of the following verses, including the words "without calculation", and according to the lexical and historical sources and reflecting on the context and structure of the verses in question, provides more accurate institutionalization and translation (Fooladvand, Ayati, Elahi Ghomshei, Mousavi Hamedani, Ansarian) has been considered. The result is that most of the above translators, in presenting the translation (Be'ghayr-i Hesāb) have used the equivalent of the hand tail (without calculation) and despite the semantic multiplicity of this phrase in different verses, have not adopted an exact equivalent for it. Ghomshei's divine translation has been used more accurately in equating than other translations. The considered equations of the phrase (Be'ghayr-i Hesāb) include "plurality", "without calculation", "without compensation", "out of material calculations", which can be deduced according to the meaning of sustenance and gift in the verse and also according to the context of the verses.